A global Fine‐Root Ecology Database to address below‐ground challenges in plant ecology. Issue 1 (28th February 2017) - Iversen, Colleen M.; McCormack, M. Luke; Powell, A. Shafer; Blackwood, Christopher B.; Freschet, Grégoire T.; Kattge, Jens; Roumet, Catherine; Stover, Daniel B.; Soudzilovskaia, Nadejda A.; Valverde‐Barrantes, Oscar J.; van Bodegom, Peter M.; Violle, Cyrille
Summary: Variation and tradeoffs within and among plant traits are increasingly being harnessed by empiricists and modelers to understand and predict ecosystem processes under changing environmental conditions. While fine roots play an important role in ecosystem functioning, fine‐root traits are underrepresented in global trait databases. This has hindered efforts to analyze fine‐root trait variation and link it with plant function and environmental conditions at a global scale. This Viewpoint addresses the need for a centralized fine‐root trait database, and introduces the Fine‐Root Ecology Database (FRED, http://roots.ornl.gov ) which so far includes > 70 000 observations encompassing a broad range of root traits and also includes associated environmental data. FRED represents a critical step toward improving our understanding of below‐ground plant ecology. For example, FRED facilitates the quantification of variation in fine‐root traits across root orders, species, biomes, and environmental gradients while also providing a platform for assessments of covariation among root, leaf, and wood traits, the role of fine roots in ecosystem functioning, and the representation of fine roots in terrestrial biosphere models. Continued input of observations into FRED to fill gaps in trait coverage will improve our understanding of changes in fine‐root traits across space and time.